STUDI KUALITATIF HUBUNGAN EKSTRAKULIKULER PANAHAN DENGAN PERKEMBANGAN MOTORIK HALUS ANAK USIA DINI - Salsabila Nur Yafi Abid Day; Dhian Gowinda Luh Safitri; Melia Dwi Widayanti; Fatiha Khoirotunnisa Elfahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the relationship between extracurricular archery activities and fine motor development in early childhood. This study used a qualitative approach with a case study design to provide in-depth insight into the phenomena occurring in the field. Data collection was conducted through observation, interviews, and documentation. The study subjects included early childhood education, archery teachers, class teachers, and parents at a kindergarten (TK) that has been providing archery extracurricular activities since 2025. Data analysis was conducted using thematic analysis techniques through a deductive approach, spanning six stages: data familiarization, initial coding, theme discovery, theme review, theme definition, and report production. The research results show that the archery extracurricular activity significantly stimulates children's fine motor development through four key themes: 1) Archery as a structured practice environment (deliberate practice), 2) Archery as an integrative sensorimotor intervention, 3) Internalization of discipline and self-efficacy, and 4) External validation and character building. The activities of holding a bow, drawing the string, and aiming at a target have been shown to effectively develop small hand muscles, improve visual-motor coordination, and extend children's attention span. These positive impacts are also observed in children's increased independence in daily activities at home and school, such as improved writing skills, cutting skills, and independent spoon-feeding skills. Thus, archery is not just a sport, but a holistic stimulation medium for preparing early childhood for academic and social readiness.